2022
DOI: 10.1021/jacs.2c01743
|View full text |Cite
|
Sign up to set email alerts
|

Atomic View of Aqueous Cyclosporine A: Unpacking a Decades-Old Mystery

Abstract: An atomic view of a main aqueous conformation of cyclosporine A (CycA), an important 11-amino-acid macrocyclic immunosuppressant, is reported. For decades, it has been a grand challenge to determine the conformation of free CycA in an aqueous-like solution given its poor water solubility. Using a combination of X-ray and single-crystal neutron diffraction, we unambiguously resolve a unique conformer (A1) with a novel cis-amide between residues 11 and 1 and two water ligands that stabilize hydrogen bond network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“… In this model, the factors that influence membrane permeability are as follows: the existence of a congruent conformation, which is a specific peptide conformation that occurs in both polar and nonpolar solvents and partitions between the two compartments, the population of the congruent conformation, the rate of interconversion between conformations, and the rate of entering (Δ G enter ) or exiting (Δ G exit ) the membrane. This model is strongly supported by the recent paper that the congruent conformers are observed even in aqueous environment (i.e., water/methanol 10:90 and 90:10) . Based on the assumption that the population of congruent conformation correlates with the population of experimentally identifiable closed conformation, the population of the closed conformation in polar and nonpolar solvents was obtained by integrating 1 H NMR spectra.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“… In this model, the factors that influence membrane permeability are as follows: the existence of a congruent conformation, which is a specific peptide conformation that occurs in both polar and nonpolar solvents and partitions between the two compartments, the population of the congruent conformation, the rate of interconversion between conformations, and the rate of entering (Δ G enter ) or exiting (Δ G exit ) the membrane. This model is strongly supported by the recent paper that the congruent conformers are observed even in aqueous environment (i.e., water/methanol 10:90 and 90:10) . Based on the assumption that the population of congruent conformation correlates with the population of experimentally identifiable closed conformation, the population of the closed conformation in polar and nonpolar solvents was obtained by integrating 1 H NMR spectra.…”
Section: Discussionmentioning
confidence: 70%
“…This model is strongly supported by the recent paper that the congruent conformers are observed even in aqueous environment (i.e., water/ methanol 10:90 and 90:10). 36 Based on the assumption that the population of congruent conformation correlates with the population of experimentally identifiable closed conformation, 35 the population of the closed conformation in polar and nonpolar solvents was obtained by integrating 1 H NMR spectra. Then, we used a ratio of the population of the closed conformation obtained in polar solvent and nonpolar solvent to quantify chameleonic behavior for each CsO derivative.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of conformational flexibility and the rates of interconversion between states for membrane permeability have been highlighted for CsA using molecular dynamics simulations. , A recent study employing a combination of X-ray and single-crystal neutron diffraction has revealed additional conformations of CsA in water/methanol mixtures …”
Section: Introductionmentioning
confidence: 99%